Improving Adolescents' Knowledge and Attitudes in Preventing Hypertension Risk Through Emo-Demo Educational Media - Rifaatul Mahmudah; Sumihardi; Neni Fitra Hayati; Erick Zicof; John Amos; Doni, Alsri Windra; Ponda, Aprizal (Jurnal Kesehatan Cendikia Jenius, 2025)
Hypertension among adolescents is an important health issue due to the increasing number of cases at a young age and the low level of knowledge regarding its prevention, thus requiring more effective educational strategies. This study aimed to determine the improvement in adolescents’ knowledge and attitudes in preventing hypertension risk through the Emo-Demo educational media. The study employed a mixed-methods design, consisting of an exploratory study for the qualitative component and a quasi-experimental one-group pretest-posttest design for the quantitative component, involving 71 adolescents selected through purposive sampling. Data were collected using questionnaires and interview guides from January 2024 to June 2025 and analyzed using the Wilcoxon test. The results showed an increase in the median knowledge score from 6.00 to 13.00 and an increase in the median attitude score from 33.00 to 40.00, with a significance value of p=0.0001. These findings indicate that Emo-Demo is effective in enhancing adolescents’ understanding and attitudes toward hypertension prevention. It is concluded that Emo-Demo can serve as a powerful educational media for adolescent health promotion and is recommended to be integrated into public health center educational programs to strengthen early prevention efforts for non-communicable diseases.